Water quality evaluation in selected coastal rivers of Tanzania using Water Quality Index - Mihale, Matobola Joel (Open Science Journal, 2022)
Quality of water in Zigi, Pangani, Ruvu, Wami, and Kizinga rivers used as drinking water sources in Tanzania was assessed using water quality index (WQI). Most geochemical water parameters in rivers deviated negatively, indicative of meeting legal specifications. However, total dissolved solids (TDS) in Ruvu River, total suspended solids (TSS) in Wami and Zigi rivers, dissolved oxygen (DO) in Pangani, Zigi, and Kizinga rivers, ammonia in Wami River, and turbidity in Wami, Zigi, and Kizinga rivers deviated positively, indicating that they are responsible for water quality changes in rivers. Higher aquatic environment index values in Wami, Pangani, Zigi, and Kizinga rivers are indicative of relatively good water environment, and vice versa in Ruvu River, indicative of anthropogenic activities. WQI indicated that quality of water in these rivers ranged from good (Pangani River) to polluted (Zigi River), while other rivers were between this range. Frequent water quality monitoring campaigns are needed.